PECTINASE PRODUCTION BY ASPERGILLUS USTUS BL5 AT SOLID STATE FERMENTATION MEDIUM USING AGRICULTURAL BIOMASS - Rahmani, Nanik; Andriani, Ade; Anggraini, Yufi Sara; Yopi, - (Teknologi Indonesia, 2013)
This research showed that Indonesian agricultural biomasses, such as Siam orange peel, Medan orange peel, Durian peel and old tea leaves contain a pectin that are a potential material for use as a substrate for pectinase production. From the four types of biomasses used, Medan orange peel produced pectinase activity with the highest value equal to 1.28 U/mL. Optimization of fermentation conditions showed that Aspergillus ustus BL5 pectinase production were affected by the concentration of substrate, media pH, and temperature of the fermentation. Optimization of process showed that the optimum substrate concentration, pH and temperatuter were 10%, 4 and 40C with pectinase activity of 1.37 U/mL, 2.85 U/mL, and 1.92 U/mL respectively. Pectin content in the medium has a proportional relationship with the activity of the enzyme pectinase produced. The high content of pectin in Medanorange peel making pectinase enzyme activity produced on the substrate is also high.